Phytochemical screening of Lycopersicum esculentum Mill. treated with seaweed liquid fertilizer - Niranjanadevi, M.; Sivakumar, K. (Journal of Drug Delivery and Therapeutics, 2018)
Premise of the study: The objective of the work is to manitor the phytochemicals present in methanolic extract of Lycopersicum esculentum after treatment with different concentrations of seaweed liquid fertilizer (SLF). Methods: In this study SLF treated L.esculentum were characterized through gas chromatography and mass spectroscopy to identify the phytochemicals constituents and functional groups of the compounds. Results: Preliminary phytochemical analysis revealed the presence of alkaloids, phenols, carbohydrates, saponins, glycosides, flavonoids, terpinoids. Among the thirty nine phytochemical constituents octa decanoic acid, stigmasterol, hexa decanoic acid and Vitamin E are relatively present in higher yield. The active phytochemical compounds and their constituents were identified with gas chromatography and mass spectrometry. The retention time, percentage of area, molecular weight and chemical formula of phytochemical compounds were determined with help of NIST08 and WILEY8 libraries. The functional groups identified from the spectrum techniques are alcohol, aldehyde, iso cyanides, alkyl compound and chloro compounds. Accordingly hexadecanic acid, beta.-amyrin, gamma sisterol, octodecanic acid, phytol, stigmasterol, vitamin E, lupeol were derived from SLF treated i.e. compared to control plants. Conclusion: The results of this study offer a platform of using SLF treated L.esculentum has an alternative source for various biological studies and it can be used as functional and pharmaceutical purposes. Keywords: SLF, Lycopersicum esculentum, Phytochemical, GC-MS and FTIR